Length Frequency Distribution, Length-Weight Relationships and Condition Factors of Nandus nandus (Hamilton, 1822) from Upper Brahmaputra Basin, Assam, NE India - Das, Jugendra Nath; Saikia, Satabdi (Asian Journal of Biological and Life Sciences)
Background: Studies on length-weight relationships and associated aspects like length frequency distribution, sex ratio and condition factors are of paramount importance for sustainable management and conservation of concerned fish species. This study was undertaken keeping in view the lack of such relevant fisheries information on Nandus nandus, a commercially important fish species from this region whose natural population has been declining considerably over the years. Aim: This study was carried out to ascertain and describe the sex ratio, length-frequency distributions (LFDs), length-weight relationships (LWRs) as well as condition factors of Nandus nandus and their seasonal variation from the floodplain wetlands of upper Brahmaputra basin, Assam. Materials and Methods: A total of 517 specimens of Nandus nandus were collected randomly between January, 2023 and May, 2024. The sex ratio was expressed as number of females divided by the number of males while length-frequency distributions were done following standard method. The LWR is determined by using the formula W= aLb and the equation Log W= Log a + b Log L (LeCren, 1951). Relative condition factor (Kn) and Fulton's condition factor (K) was calculated using the formula Kn= W/aLb and K=100W/L3, respectively. All the recorded data were presented seasonally and statistically analyzed using standard methods. Results: Observations on LFDs suggest no significant size differences between the sexes; 10-12 cm being the most dominant length group of the species. The species has a female dominant population; the females significantly outnumbered the males in all the seasons except pre-monsoon. The relationships between total length and total weight are found to be highly significant (P<0.01) and showed positive allometric growth for the species with exception in winter. The calculated b values ranged from 2.961 (post-monsoon) to 4.124 (winter) for males and from 3.101 (winter) to 3.538 (postmonsoon) for females. Calculated mean Kn value ranges between 1.00 and 1.07 with minimum seasonal variation for both the sexes while mean K value is found to be slightly higher in females than males for most part of the study. Conclusion: The findings of the present study pertaining to sex ratio, LFDs, LWRs as well as condition factors would serve as basic information towards better understanding of the biology of Nandus nandus to other workers from this region entailing further research in associated aspects of fisheries for this species.
Keywords: Condition factor; Floodplain wetlands; Length weight relationship; Length-frequency distributions; Nandus nandus; NE India; Upper Brahmaputra basin